Orexin Gene Therapy Restores the Timing and Maintenance of Wakefulness in Narcoleptic Mice - Kantor, Sandor (Associated Professional Sleep Societies, LLC, 2013)
STUDY OBJECTIVES: Narcolepsy is caused by selective loss of the orexin/hypocretin-producing neurons of the hypothalamus. For patients with narcolepsy, chronic sleepiness is often the most disabling symptom, but current therapies rarely normalize alertness and do not address the underlying orexin deficiency. We hypothesized that the sleepiness of narcolepsy would substantially improve if orexin signaling were restored in specific brain regions at appropriate times of day. DESIGN: We used gene therapy to restore orexin signaling in a mouse model of narcolepsy. In these Atx mice, expression of a toxic protein (ataxin-3) selectively kills the orexin neurons. INTERVENTIONS: To induce ectopic expression of the orexin neuropeptides, we microinjected an adeno-associated viral vector coding for prepro-orexin plus a red fluorescence protein (AAV-orexin) into the mediobasal hypothalamus of Atx and wild-type mice. Control mice received an AAV coding only for red fluorescence protein. Two weeks later, we recorded sleep/wake behavior, locomotor activity, and body temperature and examined the patterns of orexin expression. MEASUREMENTS AND RESULTS: Atx mice rescued with AAV-orexin produced long bouts of wakefulness and had a normal diurnal pattern of arousal, with the longest bouts of wake and the highest amounts of locomotor activity in the first hours of the night. In addition, AAV-orexin improved the timing of rapid eye movement sleep and the consolidation of nonrapid eye movement sleep in Atx mice. CONCLUSIONS: These substantial improvements in sleepiness and other symptoms of narcolepsy demonstrate the effectiveness of orexin gene therapy in a mouse model of narcolepsy. Additional work is needed to optimize this approach, but in time, AAV-orexin could become a useful therapeutic option for patients with narcolepsy. CITATION: Kantor S; Mochizuki T; Lops SN; Ko B; Clain E; Clark E; Yamamoto M; Scammell TE. Orexin gene therapy restores the timing and maintenance of wakefulness in narcoleptic mice. SLEEP 2013;36(8):1129–1138.